Some predictions of Rafael Lorente de Nó 80 years later - Larriva-Sahd, Jorge A. (Frontiers in Neuroanatomy, 2014)
Rafael Lorente de Nó, the youngest of Santiago Ramón y Cajal disciples, was one of the last Century´s more influential researches in neuroscience. This assay highlights two fundamental contributions of Rafael Lorente de Nó to neurobiology: the intrinsic organization of the mammalian cerebral cortex and the basic physiology of the neuron processes.